The Behavioral and Mental Health Benefits of Speaking the Heritage Language within Immigrant Families: The Moderating Role of Family Relations - Kilpi-Jakonen Elina; Kwon Hye Won (SPRINGER/PLENUM PUBLISHERS, 2025)
Understanding the development of behavioral and mental health issues among adolescents, particularly those from immigrant families, is a key area of concern. Many prior studies have focused on the role of societal (country-of-destination) language skills, but we know less about the role played by the use of the heritage language in families. We examined this latter relationship with a focus on changes in heritage language use and internalizing and externalizing problems, and how family relations moderate this relationship. We used the first two waves (2010/2011 and 2011/2012) of the Children of Immigrants Longitudinal Survey in Four European Countries (CILS4EU) data collected from Germany (n = 1614; Mage = 14.8 years, 50% female), the Netherlands (n = 1203; Mage = 14.7 years, 54% female), Sweden (n = 1794; Mage = 14.2 years, 53% female), and England (n = 1359; Mage = 14.6 years, 50% female). Our results suggest that increased use of heritage language is associated with fewer externalizing problems only in families with greater family cohesion and parental warmth (in Germany and the U.K.) and with fewer internalizing problems only in families with higher parental monitoring (in the Netherlands and Sweden). Good family relations are thus an important precondition for increased heritage language use to lead to improved behavioral and mental health for children of immigrants.